Herbivory on the Invasive Alga Caulerpa cylindracea: The Role of Omnivorous Fishes - Santamaría, Jorge; Tomas, Fiona; Ballesteros, Enric; Cebrian, Emma (Frontiers in Marine Science, 2021)
Herbivory has long been considered an important component of biotic resistance against macroalgae invasions in marine habitats. However, most of the studies on herbivory of invasive algae refer only to consumption by strictly herbivorous organisms, whereas consumption by omnivorous species has been largely ignored and rarely quantified. In this study, we assess whether the commonest omnivorous sparid species in the Mediterranean Sea are consuming the highly invasive alga, Caulerpa cylindracea, and determine both, its importance in their diet and their electivity towards it as a source of food. Our results confirm that three of the four fish species studied regularly consume C. cylindracea, but in most cases, the importance of C. cylindracea in the diet is low. Indeed, the low electivity values indicate that all species avoid feeding on the invasive alga and that it is probably consumed accidentally. However, despite animals and detritus being the main food for these sparid species, several individual specimens were found to have consumed high amounts of C. cylindracea. This suggests a potential role that these fish species, being really abundant in shallow rocky bottoms, may play in controlling, to some extent, the abundance of the invader.